SPATIAL FOREST HARVEST PLANNING CONSIDERING MAXIMUM OPERATIONAL AREAS - Augustynczik, Andrey Lessa Derci (2016)
One of the biggest challenges that forest managers face in forest planning is related to logistic issues of forest harvesting. The operational planning of forest harvesting must consider simultaneously the economic and environmental concerns, searching for increasing the efficiency and mitigating environmental damage related to the opening of forest cover. The inclusion of spatial aspects in forest harvesting is usually done through adjacency constraints. The main approaches to solve this sort of problem are ARM (Area restriction Model) and URM (Unit Restriction Model) models. In this context, the objective of this study was to perform the optimized forest planning of 236 stands of a Pinus taeda and Eucalyptus sp. forest, incorporating classical constraints like available area, timber flow, among others, and ARM and URM constraints, evaluating their effects on the optimization results. With the optimization outcomes, it is possible to conclude that ARM and URM model approaches are viable alternatives for solving forest harvest scheduling problems, being the ARM approach most suited for our case study, due to the possibility of higher profitability, while respecting maximum harvesting areas.